2016
DOI: 10.3390/ijerph13090850
|View full text |Cite
|
Sign up to set email alerts
|

25 Hydroxyvitamin D Deficiency and Its Relationship to Autoimmune Thyroid Disease in the Elderly

Abstract: Background: Low 25(OH) vitamin D levels have been associated with several autoimmune diseases and recently with autoimmune thyroiditis (AT). The aim of the study was to investigate the association of AT with low 25(OH) vitamin D levels in the elderly. Methods: One hundred sixty-eight elderly subjects (mean age: 81.6 ± 9.4 years) were enrolled. Serum levels of 25(OH) vitamin D, anti-thyroid peroxidase (TPO-Ab), anti-thyroglobulin (TG-Ab) antibodies, free triiodothyronine (FT3), free thyroxine (FT4) and thyroid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…Several clinical studies have reported a low vitamin D status in AITD or HT, indicating an association between vitamin D deficiency and thyroid autoimmunity ( Table 1 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Kivity et al, reported that the prevalence of vitamin D deficiency (25(OH)D level < 25 nmol/L) was significantly higher in 50 patients with AITD compared with 98 healthy individuals (72% vs. 30.6%; p < 0.001) as well as in 28 patients with HT compared to 42 patients with non-AITD (79% vs. 52%; p < 0.05).…”
Section: Vitamin D and Autoimmune Thyroid Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several clinical studies have reported a low vitamin D status in AITD or HT, indicating an association between vitamin D deficiency and thyroid autoimmunity ( Table 1 ) [ 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Kivity et al, reported that the prevalence of vitamin D deficiency (25(OH)D level < 25 nmol/L) was significantly higher in 50 patients with AITD compared with 98 healthy individuals (72% vs. 30.6%; p < 0.001) as well as in 28 patients with HT compared to 42 patients with non-AITD (79% vs. 52%; p < 0.05).…”
Section: Vitamin D and Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…Subgroup analyses showed that GD and HT patients also have lower 25(OH)D levels and are more likely to be deficient in vitamin D. The criterion for vitamin D deficiency in the studies included in this meta-analysis was a 25(OH)D level of <25–50 nmol/L [ 30 ]. In addition, Muscogiuri et al, studied 168 elderly subjects (mean age of 82 years) and showed a significantly higher prevalence of AITD in subjects with vitamin D deficiency (25(OH)D level < 50 nmol/L) ( p = 0.002) and a significant correlation between 25(OH)D and anti-TPO levels ( r = −0.27; p = 0.03) [ 31 ].…”
Section: Vitamin D and Autoimmune Thyroid Diseasesmentioning
confidence: 99%
“…The lack of full concordance in monozygotic twins also proves the importance of environmental factors in AITD (52, 53). Several environmental factors such as high iodine intake and vitamin D deficiency are proven to be risk factors of AITD (5458). The genetic and environmental factors may cooperate together and cause the dysfunctions of immune cells and thyroid autoimmunity, but the mechanisms involving the effects of genetic and environmental factors on the immune cells’ function and immune balance are still not well understood (5961).…”
Section: Introductionmentioning
confidence: 99%
“…Later, studies confirmed this negative association [187][188][189][190][191][192] and also reported a negative correlation between vitamin D and TgAb serum concentrations [189,191]. Several studies demonstrated that TPOAb positivity was more frequent in subjects with hypovitaminosis D compared to subjects with sufficient hormone levels [187,[193][194][195][196][197][198][199]. Further studies also demonstrated an association between the VDR polymorphisms and a higher incidence of HT, particularly VDR rs731236, rs1544410, and rs2228570 [200].…”
Section: Thyroid Autoimmunitymentioning
confidence: 81%